Physalis floridana CRABS CLAW mediates neofunctionalization of GLOBOSA genes in carpel development. (28th June 2021) - Gong, Pichang; Song, Chunjing; Liu, Hongyan; Li, Peigang; Zhang, Mingshu; Zhang, Jisi; Zhang, Shaohua; He, Chaoying
Abstract : The regulatory and genetic interactions of DOLL1, a typical floral B-function gene with PFCRC, a key carpel regulator, reveal new functional roles for floral development of P. floridana . Abstract: Floral B-function MADS-box genes, such as GLOBOSA ( GLO ), function in corolla and stamen organ identity specification. The functions of these genes outside these floral whorls are rarely reported. DOLL1 is a GLO gene controlling corolla and androecium organ identity. In this study we found that, in Physalis floridana double-layered-lantern 1 ( doll1 ) mutant pollinated with wild-type pollen, fruit set was extremely low, indicating that doll1 females are dysfunctional. Stigma and style structure, stigma receptivity, pollen tube guidance, and embryo sac development were also impaired in doll1 . P. floridana CRABS CLAW ( PFCRC ), predominantly expressed in carpels, was repressed in doll1 native carpels. Loss-of-function of PFCRC altered carpel meristem determinacy, carpel closure, and ovule number, and the resultant 'pistil' consisted of multiple spirally-arranged dorsiventral carpels occasionally with 1–2 naked ovules on the margin and trichomes at each mutated carpel tip, implying an alteration of carpel organ identity. Regulatory and genetic interactions between B-class MADS-box genes and PFCRC were revealed in a context-dependent manner in floral development. Our work reveals a new role for the B-function genes in carpel and ovule development via regulating PFCRC, providing a new understanding of genetic regulatory networks between MADS-domain and CRC transcription factors in mediating carpel organ specification, functionality, and origin.